Letter: anti‐TNF dose de‐escalation in Crohn's disease—a case‐by‐case decision. Issue 2 (15th June 2017) - Imperatore, N.; Testa, A.; Caporaso, N.; Rispo, A.
Abstract : Linked Content This article is linked to Steenbergen et al paper. To view this article visithttps://doi.org/10.1111/apt.13964 .